2022
DOI: 10.5603/cj.a2020.0027
|View full text |Cite
|
Sign up to set email alerts
|

Usefulness of soluble endothelial protein C receptor combined with left ventricular global longitudinal strain for predicting slow coronary flow: A case-control study

Abstract: This article has been peer reviewed and published immediately upon acceptance. It is an open access article, which means that it can be downloaded, printed, and distributed freely, provided the work is properly cited. Articles in "Cardiology Journal" are listed in PubMed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…Among 12 studies that measured global longitudinal systolic strain (GLSS) by 2D‐STE in all myocardial segments and full myocardial thickness and/or 3D‐STE without considering the myocardial layer, nine reported declined GLSS values in patients with CSFP 27,29–31,33,35,39–41,43,44,51 . Some studies measured GLSS based on all myocardial layers (endocardial, midmyocardial, and epicardial layers) 32,38,51 .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Among 12 studies that measured global longitudinal systolic strain (GLSS) by 2D‐STE in all myocardial segments and full myocardial thickness and/or 3D‐STE without considering the myocardial layer, nine reported declined GLSS values in patients with CSFP 27,29–31,33,35,39–41,43,44,51 . Some studies measured GLSS based on all myocardial layers (endocardial, midmyocardial, and epicardial layers) 32,38,51 .…”
Section: Resultsmentioning
confidence: 99%
“…It can, therefore, be concluded that the results of the studies measuring subendocardial layer deformation markers rather than full‐thickness deformation markers are more sensitive in demonstrating the difference between the control and patient groups. The majority of the studies concerning the LV in these conditions reported full‐thickness myocardial deformation indices, with some finding no difference between the control and patient groups 27,29–31,33,35,39–41,43,44,51 . In regard to patients with CSFP, the existing studies consistently found a reduction in the systolic function of the subendocardial and midmyocardial layers 32,38,51 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations